Series FACTS controllers in industrial low voltage electrical distribution networks for reducing fault current levels - Vishnu Charan Thippana; Alivelu Manga Parimi; Chandram Karri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In this paper, series Flexible AC transmission systems (FACTS) devices like Thyristor control series capacitor (TCSC) and Static synchronous series compensator (SSSC) with designed control logic used to reduce the fault current located in LV distribution network at the LV busbar. The electrical distribution network in small and medium scale industries such as steel plants, process and power plants is through low voltage switchgear (LVS) fed from motor control centre (MCC) switchgear through step down transformer of 11kV or 33kV/415V. The designed switchgear in the LV side for these utilities usually is at 50kA. However, the process loads are continuously increasing and sustained with additional feeders with the existing switchgear. Consequently, the fault current at the busbar of the switchgear increases which may require the replacement of entire switchgear to the new design fault current. However, upgrading the existing switchgear is not an economical solution to the industries. Alternatively reducing the fault current at the busbar is feasible. Controller design implemented for reducing the short circuit current with series FACTS devices. A study carried on 800MW Thermal power plant Ash handling LVS in ETAP and Matlab. It is observed that the results are encouraging to use series FACTS devices effectively in the LVS.